تدبير و تخدير مرض نقص التروية القلبية - إبراهيم, رزق الله; جحجاح, أكرم; صالح, حسان (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التخدير والإنعاش بالتعاون مع قسم الأمراض الباطنة خلال العام 2005- 2006 وتضمنت (50 ) مريضاً مصاباً بنقص التروية القلبية ( IHD ) Ischemic Heart Disease وهؤلاء المرضى مبرمجون من أجل الخضوع لعمل جراحي لا قلبي. كان الهدف من البحث هو استخلاص أفضل السبل التي يجب اتباعها من أجل تحضير وتخدير مرضى نقص التروية القلبية بحيث نضمن حصول الحد الأدنى من الاختلاطات عند هؤلاء المرضى حيث إنّ التوازن بين حاجة القلب من الأكسجين وما هو مقدم إليه هو توازن هش ومعرض للانكسار عند أية شدة تخديرية أو جراحية. تم تخدير( 25) مريضاً تخديراً عاماً و( 25 ) مريضاً تخديراً شوكياً أو فوق الجافية, وتبين لدينا من خلال هذه الدراسة أن المرضى المتابعين لأدويتهم القلبية بانتظام والمقلعين عن عوامل الخطورة والمحضرين دوائياً بشكل جيد قبل العمل الجراحي هم أقل المرضى تعرضاً للاختلاطات والوفيات بعد العمل الجراحي. This study was carried out in the Department of Anesthesia and Reanimation in collaboration with the Department of Internal Diseases at Al–Assad University Hospital, Lattakia, during the year 2005-2006, and included fifty patients who had ischemic heart disease (I H D). These patients were programmed to undergo no cardiac surgical work. The aim of the study was getting on the best methods which have to be followed for preparation and anesthesia of ischemic heart patients in order to reduce a lot of complications for these patients. This is because the balance between the need of heart for oxygen and what is given to it is very soft and is likely to break at any surgical or anesthetic stress. 25 patients were anesthetized general anesthesia and 25 patients spinal or epidural. We found out that the patients who kept taking their heart drugs regularly were away from the factors of danger and were prepared in medical ways very well before any surgical work. All these were less exposed to complications and death after surgical work.